(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper analyses three south-eastern Iberian inscriptions from Castellar de Meca (Ayora, Valencia): the first is a painted inscription brought by Pierre Paris to the Louvre Museum in the early twentieth century; the others are two small unpublished inscriptions from a private collection: a small lead sheet and a small ceramic ostrakon. In the case of the painted in-scription, we propose an alternative reading more respectful with the text palaeography. In the case of the text of the lead sheet, although it only contains three signs, clear parallels with the lead plaque of Llano de la Consola-tion (Montealegre del Castillo, Albacete) can be established. Finally, the meaning of the ostrakon text could be of metrological type.